1997
DOI: 10.1097/00003246-199707000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Serum neuron-specific enolase as early predictor of outcome after cardiac arrest

Abstract: In patients who have been resuscitated after cardiac arrest, serum neuron-specific enolase concentrations of >33 ng/mL predict persistent coma with a high specificity. Values below this cutoff level do not necessarily indicate complete recovery, because this method has a sensitivity of 80%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
3
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 32 publications
7
71
3
6
Order By: Relevance
“…Alternatively, high serum NSE levels may reflect the extent of the neuronal damage. One piece of evidence which can support this hypothesis is the relationship between the degree of neuronal damage and the serum NSE level following a cerebral stroke (Cunningham et al, 1991(Cunningham et al, , 1996DeGiorgio et al, 1995DeGiorgio et al, , 1999Fogel et al, 1997;Missler et al, 1997;Martens et al, 1998;Buttner et al, 1999;Schoerkhuber et al, 1999;Wunderlich et al, 1999) or other neuronal brain damage (DeGiorgio et al, 1995(DeGiorgio et al, , 1999Fogel et al, 1997;Martens et al, 1998; Buttner et al, 1999;Schoerkhuber et al, 1999). In these diseases, the serum NSE level exhibits a prognostic indication inasmuch as studies have found a close relationship between the volume of affected neuronal tissue and the serum NSE level (Cunningham et al, 1991(Cunningham et al, , 1996Missler et al, 1997;Wunderlich et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, high serum NSE levels may reflect the extent of the neuronal damage. One piece of evidence which can support this hypothesis is the relationship between the degree of neuronal damage and the serum NSE level following a cerebral stroke (Cunningham et al, 1991(Cunningham et al, , 1996DeGiorgio et al, 1995DeGiorgio et al, , 1999Fogel et al, 1997;Missler et al, 1997;Martens et al, 1998;Buttner et al, 1999;Schoerkhuber et al, 1999;Wunderlich et al, 1999) or other neuronal brain damage (DeGiorgio et al, 1995(DeGiorgio et al, , 1999Fogel et al, 1997;Martens et al, 1998; Buttner et al, 1999;Schoerkhuber et al, 1999). In these diseases, the serum NSE level exhibits a prognostic indication inasmuch as studies have found a close relationship between the volume of affected neuronal tissue and the serum NSE level (Cunningham et al, 1991(Cunningham et al, , 1996Missler et al, 1997;Wunderlich et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…11 Therefore, recent attention focuses on biochemical markers of hypoxic brain damage. [13][14][15][16]22 To be an ideal marker for brain injury, the marker should be proved to be released from neurons or glial cells in experimental settings, for example cell cultures. Such proofs exist for NSE 32 but not for S-100.…”
Section: Discussionmentioning
confidence: 99%
“…NSE, however, also exists in platelets and in erythrocytes, and there is a constant turnover of NSE in blood, making changes specifically associated with brain damage in serum levels difficult to evaluate. 14,16 Moreover, it is well known that platelets are markedly activated and hemolysis may occur during early reperfusion after cardiac arrest. 33 Therefore, even though at least a proportion of NSE is released from neurons, the determination of NSE, particularly during early reperfusion after cardiac arrest, may not be brain specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A NSE tem meia-vida de aproximadamente 24h 29 . Um estudo importante que marcou o início da investigação da NSE como indicador de prognóstico da extensão da isquemia cerebral em pacientes em coma pós-PCR foi o de Fogel e col. no final da década de 1990 30 . Nesse estudo, foram feitas dosagens diárias de NSE durante sete dias pós-reanimação em 43 pacientes coronarianos.…”
Section: A Enolase Específica Do Neurôniounclassified